TRADITION OF EID AL-FITR ALMSGIVING: IMPLEMENTATION IN COMMUNITY LIFE IN THE VILLAGE OF TANAH PERIUK - ayu ramadhani; Suyato (SOSIOEDUKASI, 2025)
ABSTRACT This study discusses the implementation of Pancasila values in the Sedekah Lebaran tradition in Tanah Periuk Village, Muara Beliti Subdistrict, Musi Rawas Regency. This tradition arose from the social needs of an agrarian community that in the past rarely had time to interact due to their busy farming schedules, so that during Eid al-Fitr and Eid al-Adha, collective activities were held to strengthen relationships, maintain solidarity, and reinforce unity. The research used a descriptive qualitative method with an ethnographic approach, through interviews, participatory observation, and documentation. The results of the study show that the Sedekah Lebaran tradition is a tangible manifestation of the implementation of all five principles of Pancasila: the first principle through communal prayer, the second principle in the attitude of mutual forgiveness and equal treatment of all citizens, the third principle in community unity without discrimination, the fourth principle in deliberation and collective agreement to preserve traditions, and the fifth principle through mutual cooperation and equal visits to every house. This tradition not only serves as a cultural heritage, but also as a medium for moral, spiritual, and national education that is relevant in the midst of modernisation, while also demonstrating the integration between Islamic teachings and local wisdom in creating social harmony. KEYWORDS culture, Pancasila, Sedekah Lebaran, tradition, solidarity